2015
DOI: 10.4278/ajhp.130731-quan-393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Work Environment on Using Time at Work to Exercise

Abstract: The results support the hypothesis that individuals with a supportive work environment would be more likely to use time at work to exercise. Workload and having time during the day are more important than job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Bale et al (2015) conducted a quantitative analysis of environmental barriers to 30 minutes of daily exercise provided in paid work time. (38) They found that those who reported having too much work were three times less likely to use their PA time than others who reported having more manageable workloads. Managers in the present study also noted a similar concern with regards to the potential cost of lost time with employees potentially working less time each day.…”
Section: Discussionmentioning
confidence: 99%
“…Bale et al (2015) conducted a quantitative analysis of environmental barriers to 30 minutes of daily exercise provided in paid work time. (38) They found that those who reported having too much work were three times less likely to use their PA time than others who reported having more manageable workloads. Managers in the present study also noted a similar concern with regards to the potential cost of lost time with employees potentially working less time each day.…”
Section: Discussionmentioning
confidence: 99%
“…When discussing potential barriers of PA in paid work time for employees, high workload was noted as the most significant barrier across all workplaces and employees. Bale et al (2015) conducted a quantitative analysis of environmental barriers to 30 min of daily exercise provided in paid work time [38]. They found that those who reported having too much work were three times less likely to use their PA time than others who reported having more manageable workloads.…”
Section: Discussionmentioning
confidence: 99%
“…For example, managerial support for employees to participate during work time has been shown to be associated with a higher likelihood of participation in physical activity programs. 27 From an implementation perspective, respondents were more likely to participate if they felt they were consulted, that the programs were relevant or interesting, helpful or convenient to participate in. Relatively few respondents reported that they were consulted, despite consultation being a key implementation strategy that agencies were recommended to use.…”
Section: Discussionmentioning
confidence: 99%